Growth Rate, Ration, and Temperature Effects on Otolith Elemental Incorporation - Miller, Jessica A.; Hurst, Thomas P. (Frontiers in Marine Science, 2020)
The application and utility of otolith chemistry continues to expand despite an incomplete understanding of the mechanisms that regulate elemental incorporation. An unresolved question is what role individual factors such as growth play in regulating elemental incorporation. Disentangling growth variation from thermal effects is particularly challenging in fishes yet integral to understanding the mechanisms of incorporation and interpreting patterns of variation in the field. Juvenile Pacific cod (Gadus macrocephalus) were maintained in a controlled laboratory setting to evaluate the relative importance of growth rate, ration, and temperature on otolith elemental incorporation. Fish were held at four temperatures (2, 5, 9, 13 C) and fed daily to apparent satiation. An additional treatment included fish that were held at 9 C and fed a reduced ration (1% body mass d-1). Fish were maintained for variable duration (40-147 d), depending on ration and temperature, to ensure adequate otolith growth for analysis. Water samples for chemical analysis were collected to determine elemental partition coefficients (DMe). Overall, mean growth rates ranged from -0.09 to 1.52% d-1. For the 9 C fish, there was a clear ration effect on DMn (2.6X higher at high ration) and DSr (1.5X higher at low ration), a small effect for DMg (1.1X), and no effect for DBa. For high ration fish, there was a positive effect of temperature on DMn and DMg, due solely to differences in the 2 C treatments, and no effect on DSr and DBa. Correlations between growth and DMe within temperature treatments were variable but, for DMn and DSr, the directionality mirrored the ration effect with positive correlations for DMn and negative correlations for DSr. Overall, the observed ration effects were greater than any growth rate effect, indicating that the effect of ration accounts for more than growth variation.